0860 Burst Suppression due to Diffuse Encephalopathy. (25th May 2022) - Pandey, Shilpa; Coorg, Rohini; Mohan, Sherrill; Kaplan, Kevin
Abstract: Introduction: Burst suppression is a finding on electroencephalography (EEG) associated with a severe encephalopathy associated with coma, severe infantile-onset epilepsy syndromes, hypothermia, or may be medically induced by general anesthesia. It presents as a pattern of alternating high-voltage, 75-250µV, activity separated by periods of amplitude dampening, less than 5µV, of electrical brain activity1. The duration of the burst's activity is 1-20 seconds while the suppression lasts longer than 10 seconds1. When not medically induced, burst suppression is a known marker of poor prognosis. Report of Cases: An 18-year-old male with cerebral palsy, spastic quadriplegia, and static encephalopathy secondary to hypoxemia ischemic injury in the perinatal period presents with excessive sleepiness during therapy sessions. He was empirically placed on non-invasive ventilatory support with BPAP ST 8/4 cm H2O with a rate of 10 breaths per minute for chronic respiratory failure during sleep. While awake he shows no evidence of hypoxemia or hypercapnia on room air. A polysomnogram was ordered showing moderate obstructive sleep apnea (oAHI 9.73) and central sleep apnea (5.84 events per hour) without hypoxemia (SpO2 nadir 90%), or hypercapnia (TcCO2 max 48 mmHg). The study was scored as REM/NREM as specific sleep architecture was not identified. Diffuse burst suppression was observed. No epileptiform abnormalities were recorded. A MRI of the brain shows diffuse encephalomalacia involving the supratentorial brain parenchyma with volume loss of the cerebellum, the pons, and brain stem. Conclusion: The abnormal brain activity noted in our patient is due to underlying encephalomalacia and diffuse brain injury secondary to his perinatal hypoxemic ischemic injury. Despite his significant underlying neurological abnormality, he can maintain adequate ventilation and oxygenation while awake. While asleep, he has moderate obstructive and central sleep apnea without hypoxemia or hypercapnia. This is likely due to the activity of control centers of respiration being spared despite the volume loss noted on the brain MRI. Support (If Any): References:1) Bhattacharyya, Sourya; Biswas, Arunava; Mukherjee, Jayanta; Majumdar, Arun Kumar; Majumdar, Bandana; Mukherjee, Suchandra; Singh, Arun Kumar (1 November 2013). "Detection of artifacts from high energy bursts in neonatal EEG". Computers in Biology and Medicine. 43 (11): 1804–1814.2) Lee, Jaeyun; Song, Woo-Jin; Lee, Hyang-Woon; Shin, Hyun-Chool (2016). "Novel Burst Suppression Segmentation in the Joint Time-Frequency Domain for EEG in Treatment of Status Epilepticus". Computational and Mathematical Methods in Medicine. 2016.